Storage of crioula and bola precoce onions under refrigeration and controlled atmosphere - Schorr, Marcio Renan Weber (2013)
Take into account the crescent consumers demand by quality foods and the need of constant supply of vegetables products, the aim of this study was to evaluate the conservation of Crioula and Bola Precoce onions stored in different controlled atmosphere (CA), relative humidity (RH), temperature and ethylene conditions. Were evaluated four experiments with cv. Crioula and one with cv Bola Precoce. In the Crioula experiment 1, was tested the effect of different O2 and CO2 levels in storage atmosphere, two RH and two temperatures levels. Crioula experiment 2 tested three RH levels (75, 80 and 85%), experiment 3 tested three temperature levels (0.5, -0.5 and -1.0 °C) and experiment 4 tested the effect of presence or absence of ethylene 10 μl l-1, all in cold storage (CS). Bola Precoce experiment conditions are identical to Crioula experiment 1. The analyses were realized after six months of storage. CA decreased the breaking of dormancy and the bulb sprout onset in relation to CS. Low O2 and high CO2 increased the response from CA on sprout development process. Respiratory rate of bulbs gradually decreased during shelf-life, being less in CA stored bulbs. The mainly form of mass loss was due to respiration in Crioula and due to water loss in Bola Precoce . CA, mainly with 0.5+2.0 (kPa O2+kPa CO2), reduced aliinase activity and the generation of precursor compounds of onion flavor, beyond decrease the soluble solids consume and polyphenols level. Therefore, CA decrease the bulb metabolism during storage, reflecting in retard in breaking of dormancy and sprout onset, beyond maintain better post-harvest bulb quality. Better results were obtained in AC 0.5+2.0 (kPa O2+kPa CO2).